2017
DOI: 10.18632/oncotarget.22740
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of mitochondrial biogenesis promotes disease progression in multiple myeloma

Abstract: Many cancers, including multiple myeloma (MM), retain more cytosolic iron to promote tumor cell growth and drug resistance. Higher cytosolic iron promotes oxidative damage due to its interaction with reactive oxygen species generated by mitochondria. The variation of mitochondrial biogenesis in different stages of MM disease was evaluated using gene expression profiles in a large clinical dataset. Sixteen of 18mitochondrial biogenesis related gene sets, including mitochondrial biogenesis signature and oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Recently, Zhan et al demonstrated that gene expression of mitochondrial biogenesis signatures were significantly higher in relapsed and drug resistant myeloma samples than newly diagnosed patient samples. Inhibition of mitochondria OXPHOS dramatically reduced the growth of MM xenograft in in vivo model [168]. Similar results were reported by Alejandra Ortiz-Ruiz and colleagues [169].…”
Section: The Role Of Nrf2 In Mitochondrial Regulation In Myelomasupporting
confidence: 85%
“…Recently, Zhan et al demonstrated that gene expression of mitochondrial biogenesis signatures were significantly higher in relapsed and drug resistant myeloma samples than newly diagnosed patient samples. Inhibition of mitochondria OXPHOS dramatically reduced the growth of MM xenograft in in vivo model [168]. Similar results were reported by Alejandra Ortiz-Ruiz and colleagues [169].…”
Section: The Role Of Nrf2 In Mitochondrial Regulation In Myelomasupporting
confidence: 85%
“…In relapsed and refractory patients MM PCs overexpress mitochondrial biogenesis signatures regulated by the cellular iron content ( 133 ). The consequent loss of integrity of redox balance, with the nuclear compartmentalization of heme-oxygenase 1 is associated to drug resistance and genomic instability ( 134 ).…”
Section: Mitochondrial Fitness Mediates Resistance To Bortezomib In Mmentioning
confidence: 99%
“…As far as the case described by Antonucci et al (2019b) is concerned, it is worth considering that this neoplasia is among those that accumulate iron, a metal essential to promote cancer cell growth and resistance to chemotherapy. High levels of iron in the cytosol react with ROS produced by defective mitochondria in cancer cells and this leads to further oxidative damage (Zhan et al, 2017). It is therefore plausible that the encouraging results reported by (Antonucci et al, 2019b) may be ascribed also to the restoration of mitochondrial functionality associated with detoxification of metals as also described in (Blythe et al, 2017).…”
Section: Resultsmentioning
confidence: 82%